Integrating Local Culture in Higher Education: Foundation of Indonesia’s National Identity - Mustaqim Pabbajah; Juhansar Juhansar; Ratri Nurina Widyanti; Widi Fajar Widyatmoko; Mohammad Faizal Al Ghozali (Proceeding of the International Conference on Global Education and Learning, 2025)
Local culture plays a strategic role in shaping and maintaining the identity of the diverse Indonesian nation. In the context of higher education, local culture does not merely function as a heritage of tradition but also as a source of values and character that can strengthen students’ national consciousness. This research aims to analyze the role of local culture as the foundation of national identity at the university and to identify strategies for implementing cultural values in the educational process and at campus life. This research employes a descriptive qualitative approach using interviews, Focus Group Discussions (FGDs), participatory observation, and document analysis to collect data. The findings indicate that the internalization of local cultural values through curriculum, student activities, and academic culture can strengthen the self-identity of students as the nation’s next generation. Thus, higher education institutions play a crucial role as agents of cultural preservation while simultaneously driving national ideology through the development of academic and non-academic programs rooted in local values. Thus, strengthening local culture in higher education is a strategic step in building a national identity that is characterized, competitive, and uniquely Indonesian.